The therapeutic effect of ceramic art-assisted drug therapy on hyperactivity disorder in children - Shi, Fuxia; Chen, Enze (CNS spectrums, 2023)
BackgroundHyperactivity disorder in children is a common neurodevelopmental disorder that seriously affects children’s learning and quality of life. Therefore, it is clinically important to find new treatment methods.Subjects and MethodsThe study selected 100 cases of pediatric patients in a hospital between March 2021 and January 2022. They were randomly divided into an observation group and a control group, with 50 cases in each group. The observation group received ceramic art-assisted drug therapy, and the control group received conventional drug therapy. By observing and recording the anxiety scores, attention scores, and behavioral problems scores of the study subjects during the treatment process, while using SPSS22.0 software for data analysis, the differences in the treatment effects of the two groups were compared and tested for significance.ResultsThe mean values of anxiety scores decreased by 30.26% and 15.49%, the mean values of attention scores increased by 20.26% and 11.54%, and the mean values of behavioural problem scores decreased by 24.06% and 18.83% in the observation group and the control group, respectively, after treatment. The observation group was better than the control group in anxiety scores, attention scores and behavioural problem scores, and the differences were all statistically significant (P<0.05).ConclusionsCompared with conventional medication, ceramic art-assisted medication can significantly reduce anxiety scores, improve attention scores and reduce behavioural problems, which has clinical promotion and application value.